Development of a morphing wingtip based on compliant structures. (September 2018) - Wang, Chen; Haddad Khodaparast, Hamed; Friswell, Michael I; Shaw, Alexander D; Xia, Yuying; Walters, Peter
Compliant structures, such as flexible corrugated panels and honeycomb structures, are promising structural solutions for morphing aircraft. The compliant structure can be tailored to carry aerodynamic loads and achieve the geometry change simultaneously, while the reliability of the morphing aircraft can be guaranteed if conventional components and materials are used in the fabrication of the morphing structure. In this article, a compliant structure is proposed to change the dihedral angle of a morphing wingtip. Unsymmetrical stiffness is introduced in the compliant structure to induce the rotation of the structure. Trapezoidal corrugated panels are used, whose geometry parameters can be tailored to provide the stiffness asymmetry. An equivalent model of the corrugated panel is employed to calculate the deformation of the compliant structure. To provide the airfoil shape, a flexible honeycomb structure is used in the leading and trailing edges. An optimisation is performed to determine the geometry variables, while also considering the actuator requirements and the available space to instal the compliant structure. An experimental prototype has been manufactured to demonstrate the deformation of the morphing wingtip and conduct basic wind tunnel tests.